2008
DOI: 10.1007/s00429-008-0197-x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of catecholamine on the migration of gonadotropin-releasing hormone-producing neurons in the rat foetuses

Abstract: Catecholamines (CA) play an important role in the regulation of GnRH neurons in adults, and it is probable that they control GnRH-neuron development. Migration of GnRH neurons was evaluated in male and female rats at the 17th embryonic day (E17) and E21, following the daily treatment of their pregnant mothers from the 11th to the 16th and 20th day of gestation with alpha-methyl-para-tyrosine (alphaMPT), an inhibitor of catecholamine synthesis. High-performance liquid chromatography with electrochemical detecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 63 publications
(67 reference statements)
0
9
0
Order By: Relevance
“…The sympathetic nervous system neurotransmitters and catecholamines, especially norepinephrine, play important roles in the regulation of GnRH neurons; therefore it is possible that they also control GnRH neuron development in ontogenesis (39,40), which is an important step in the secretion of GnRH (41).…”
Section: Urinary Metabolites From Triptorelin and Derivatives-trip-mentioning
confidence: 99%
“…The sympathetic nervous system neurotransmitters and catecholamines, especially norepinephrine, play important roles in the regulation of GnRH neurons; therefore it is possible that they also control GnRH neuron development in ontogenesis (39,40), which is an important step in the secretion of GnRH (41).…”
Section: Urinary Metabolites From Triptorelin and Derivatives-trip-mentioning
confidence: 99%
“…The close topographic location of GnRH-immunoreactive neurons and TH-immunoreactive nerve fibers was observed in the nucleus accumbens on days 17 and 20 and in the median eminence on day 20. A quantitative radioimmunoassay for GnRH in the caudal regions of the GnRH neuron migration route in 21-day rat fetuses showed that injection of MPT resulted in a drop of GnRH level in the anterior hypothalamus of female fetuses (Izvolskaia et al, 2009). This is additional evidence that catecholamines contribute to the regulation of development of GnRH neurons during prenatal ontogeny.…”
Section: Neuroendocrine and Immune Regulatory Mechanisms In The Develmentioning
confidence: 88%
“…There is evidence that embryonic GnRH neurons and other topographically close neurons transiently expressing TH may also be involved in local metabolism of catecholamines. According to our data, suppression of catecholamine synthesis in rat embryos by alphamethyl-p-tyrosine ( MPT, a competitive TH inhibitor) beginning from day 11 of development leads to an increase in the number of GnRH neurons in the rostral segments of their migration route by day 17 and their accumulation in the zone of their entry into the forebrain by days 18-21 (Izvolskaia et al, 2009). Experiments with double immunohistochemical labeling allowed us to determine the regions of interaction of the catecholaminergic brain systems with migrating and differentiating GnRH neurons.…”
Section: Neuroendocrine and Immune Regulatory Mechanisms In The Develmentioning
confidence: 92%
See 1 more Smart Citation
“…16-µm cryostat sections of brains were mounted onto slides, heated at 65°C to inhibit endogenous phosphatases, and incubated with a mixture of chromogenic enzyme substrates containing nitroblue tetrazolium and 5-bromo-4-chloro-3-indolyl phosphate (NBT/BCIP) in the appropriate buffer. Anti-GnRH rabbit polyclonal antibody (a kind gift from Dr. Tillet, Nouzilly, France) has been previously characterized [11,31,32,33]. It was used at 1/5,000 to 1/10,000 dilutions then revealed with Alexa488-conjugated secondary antibody.…”
Section: Methodsmentioning
confidence: 99%